2020
DOI: 10.1093/ajcn/nqaa190
|View full text |Cite
|
Sign up to set email alerts
|

Maternal dietary intake of fish and PUFAs and child neurodevelopment at 6 months and 1 year of age: a nationwide birth cohort—the Japan Environment and Children’s Study (JECS)

Abstract: Background Although emerging evidence indicates a relation between maternal intake of fish and improved child neurodevelopment, the results are inconsistent. Objectives This study investigated whether dietary consumption of fish during pregnancy is associated with offspring neurodevelopment at age 6 mo and 1 y. As exploratory research, we also examined the association between consumption of PUFAs and neurodevelopment at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…The ASQ-3 is a set of well-validated, globally used questionnaires that is recommended by the United Nations Children’s Fund to identify potential delays and help determine which children need further assessment or ongoing monitoring [ 15 ]. The Japanese version of the ASQ-3 has also been validated [ 16 ] and has already been used in previous studies [ 17 , 18 , 19 ]. The ASQ-3 assesses the following five areas of development: (1) Communication: Language skills, such as babbling, vocalizing, listening, and understanding; (2) gross motor: Arm, body, and leg movements to move and play; (3) fine motor: Hand and finger movements; (4) problem solving: Problem-solving skills, learning, and playing with toys; (5) personal-social: Self-help skills, solitary social play, and play with toys and others.…”
Section: Methodsmentioning
confidence: 99%
“…The ASQ-3 is a set of well-validated, globally used questionnaires that is recommended by the United Nations Children’s Fund to identify potential delays and help determine which children need further assessment or ongoing monitoring [ 15 ]. The Japanese version of the ASQ-3 has also been validated [ 16 ] and has already been used in previous studies [ 17 , 18 , 19 ]. The ASQ-3 assesses the following five areas of development: (1) Communication: Language skills, such as babbling, vocalizing, listening, and understanding; (2) gross motor: Arm, body, and leg movements to move and play; (3) fine motor: Hand and finger movements; (4) problem solving: Problem-solving skills, learning, and playing with toys; (5) personal-social: Self-help skills, solitary social play, and play with toys and others.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to fruit, vegetables and the vitamins contained in them, several previous studies reported that fish and polyunsaturated fatty acids such as docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) were beneficial for neurodevelopment in offspring (5,6) . Comparing fish and unsaturated fatty acid consumption by quartiles of fruit and vegetable consumption, the higher the quartile of vegetable consumption, the higher the fish and unsaturated fatty acid consumption (Tables S2-S5).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Diet during pregnancy has a close relationship with the development of the child. It has been reported that fish, polyunsaturated fatty acid, folic acid and multivitamins intake before and during pregnancy have a positive effect on the offspring's neurological development (5)(6)(7)(8)(9) . Fruit and vegetables are major sources of vitamins and minerals, but the association between fruit and vegetable consumption before and during pregnancy and offspring's neurological development has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific reports have described the health benefits of consuming fishery and fish products especially towards reduced risk of death from heart disease such as coronary heart disease and stroke (Trivedi et al, 2021, Tani et al, 2021, Forouhi et al, 2018, WHO & FAO, 2011, reduction in the risks of diabetes (Chen et al, 2021), improved visual and cognitive development as well as increased duration of gestation (Hellberg et al, 2012), improved neurodevelopment in infants and children when fish is consumed before and during pregnancy (Hamazaki et al, 2020), and finally, reduction the risks of thyroid cancer (Cléro et al, 2012).…”
Section: Importance Of Aquaculturementioning
confidence: 99%